The effect of cigarette advertising on smoking behaviour of students in Banda Aceh City, Indonesia - Putra, Heru Syah; Rosemary, Rizanna; Yanuar, Deni; Ahsan, Abdillah (Penerbit Universiti Kebangsaan Malaysia, 2020)
The prevalence of student smokers has been increasing in Banda Aceh City recently. The presence of cigarette advertisements near schools is believed to be one of the causes. However, there is a lack of study for this issue. This study tries to calculate the effect of cigarette advertisements around schools on the smoking activities of students. This research is conducted in the city of Banda Aceh with a total sample of 365 students. We use the Linear Probability Model to estimate the effect by assuming that smoking behaviour is a factor of individual, household and environmental characteristics of students. The result shows that cigarette advertising has a positive and significant effect on the smoking behaviour of high school students in Banda Aceh. The presence of cigarette billboards near the school increases the probability of students’ smoking behaviour by 12.4%, whereas the presence of banners causes an increase in the probability by 18.4%. It shows that 41% of the samples are smokers or had smoked before with 37% daily smokers and 59% occasional smokers. Through in-depth interviews, this study finds that having a smoker father or brother as well as friend increases the willingness of students to be smoker. Therefore, the local government should undertake a policy to ban cigarette advertisements in order to reduce the students’ risk of being smokers. The government must also promote the creation of smoke-free families to reduce the possibility of increasing student smoker rate.